Molecular cloning of a polymorphic DNA endonuclease fragment associates insulin-dependent diabetes mellitus with HLA-DQ. - Michelsen, B (1987)
A BamHI 3.7-kilobase (kb) fragment detected by an HLA-DQ beta-chain complementary DNA (cDNA) probe and negatively associated with insulin-dependent diabetes mellitus (IDDM) was cloned and sequenced to localize the polymorphism to BamHI sites in intervening sequences of an HLA-DQ beta-chain gene. A probe of the first intervening sequence (IVS 1) showed the BamHI 3.7-kb fragment in 6 of 17 HLA-DR3/4 controls but in 0 of 13 DR-identical IDDM patients. All IDDM patients (13 of 13) had BamHI fragments of 12 and 4 kb, detected in 9 of 17 controls (P less than 0.02). The simple restriction fragment length polymorphism pattern of the IVS 1 probe was exploited by comparing 113 IDDM patients with 177 healthy controls to show increased prevalences in IDDM of the 12-kb (P less than 0.0001) and 4-kb (P less than 0.0001) fragments. In IDDM patients younger than 20 yr at onset, 98% were 12- and/or 4-kb positive, compared with 63% of controls (P less than 0.0001), giving a relative risk of 91.8 for individuals with both fragments. The 12-kb fragment was linked to HLA-DR4, and the 4-kb fragment to HLA-DR3. Both serologic markers were split and a non-DR3/non-DR4 IDDM patient was 4-kb positive. HLA-DQ seems therefore closer, than HLA-DR, to an IDDM susceptibility gene.